JURIDICAL NORMATIVE REVIEW OF CONVERSION CONVENTIONAL BANKS INTO ISLAMIC BANK AFTER THE PROMULGATION OF QANUN ACEH CONCERNING SHARIA FINANCIAL INSTITUTIONS - Fahrul Fauzi (Faculty of Social and Political Sciences University of Bangka Belitung, 2020)
Nowadays, Islamic banks in Indonesia continue to experience growth, one of which is in the Province of Nanggroe Aceh Darussalam. In Aceh, in order to support Islamic financial institutions, Qanun No. 11 of 2018 concerning Islamic Financial Institutions has been formed. It is interesting to review the provisions of Article 65 which reads